Plasmacytoid dendritic cells and regulatory T cells in the tumor microenvironment: A dangerous liaison - Conrad, Curdin (Landes Bioscience, 2013)
Tumor-infiltrating plasmacytoid dendritic cells (pDCs) have been associated with poor patient prognosis. We have recently uncovered the ability of pDCs to activate and expand a subset of tumor-infiltrating FOXP3(+) regulatory T cells that express inducible costimulator (ICOS), providing new insights into the mechanisms that govern the escape of cancer from immunosurveillance.